2006
DOI: 10.1002/pola.21826
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical and electrochemical properties of copolymers consisting of 9,9‐dihexylfluorene and aromatic triazole chromophores

Abstract: Aromatic triazole chromophores were incorporated into polyfluorene in an attempt to increase electron affinity, to promote emission efficiency, and to diminish excimer formation. Poly(9,9-dihexylfluorene) (P1) and new copolymers with aromatic triazoles (P2-P4) were prepared by Suzuki coupling polymerization. In P2, the aromatic triazole (3.8 mol %) was attached exclusively as terminal groups, whereas P3 and P4 were main-chain copolymers containing 3.9 and 10.3 mol % aromatic triazole chromophores, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Another widely employed method is to enhance electron affinity of the conjugated polymers by incorporating electron affinitive groups 26. The aromatic triazole group is an interesting electron‐injection/transport group because of its high‐electron‐affinity and thermal stability 27‐29. To achieve a good balance of holes and electrons, both hole‐ and electron‐transporting functions should be incorporated into a single bipolar material 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…Another widely employed method is to enhance electron affinity of the conjugated polymers by incorporating electron affinitive groups 26. The aromatic triazole group is an interesting electron‐injection/transport group because of its high‐electron‐affinity and thermal stability 27‐29. To achieve a good balance of holes and electrons, both hole‐ and electron‐transporting functions should be incorporated into a single bipolar material 30–32.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that photo-generated excitons are dissociated at the interface between two components and efficient charge transfer occurs, leading to less emission. Scheme 2 exhibits the corresponding electronic energy levels for PFH [21] and NDI-BA. The lowest unoccupied molecular orbital (LUMO) level of NDI-BA was estimated as À3.8 eV by cyclic voltammetry.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…One of the strategies to improve efficiency of PLED is to synthesis new efficient polymers with electron transporting materials. It has been continuously reported that the S-conjugated polymers containing 1,3,4-oxadiazole (OXD), 2-7 1,2,4-triazole (TAZ) [8][9][10] in the main chain or side chain to improve device efficiency. Because the most of Sconjugated polymers have good hole injection/transporting properties.…”
Section: Introductionmentioning
confidence: 99%